Metaplastic Carcinoma Breast in Polycythemic Octogenarian – Lessons Learnt: Case Report - Prabhu, Swarup; Malhotra, Munish; Saidha, Naresh; Mehta, Ritu; Dwivedi, Surjeet; Gupta, Tarun Mohan (Lietuvos chirurgija, 2024)
An 80-year-old lady presented with lump Left breast of 8 months duration. Clinically was aT4b lesion, sonomammogram showed BIRADS V lesion and core needle breast biopsy features were suggestive of metaplastic carcinoma breast of adenosquamous type, ER, PR-Positive, Her2Neu-Negative. Patient received preoperative hormonal therapy followed by modified radical mastectomy and postoperative adjuvant chemotherapy and hormonal therapy. Post operative patient showed good clinical recovery and was recurrence free at 6 months follow up although patient had all the poor prognostic factors with large size, LN involvement and high Ki 67. This article is a rare example of metaplastic breast carcinoma presenting in geriatric age group and showing good recovery despite presence of all poor prognostic factors. Hence this report is to enlighten the medical caregivers about the existence of this rare entity and challenges involved in management of this entity.